STRATEGI KOOPERATIF GABUNGAN JIGSAW IV-RECIPROCAL TEACHING DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF BIOLOGI SISWA SMA DI JEMBER - Suratno, Suratno (BIOEDUKASI (Jurnal Pendidikan Biologi), 2010)
The learning achievement is important aspect on biology learning. This study aims at finding out the effect of the learning strategy toward the cognitive learning achievement.This study was quasy experimental design. The procedure of the experimental study was pretest-posttest nonequivalent control group design. The population of this study was the 10th grade students of 2008/2009 academic year of the public and private senior high schools in Jember. The cognitive learning achievement was measured by adopting a test of essay. Before using the instruments, they were tried out to get validity, reliability, level of difficulty, and the different weight. The data analysis by covariance (ancova) that were taken place at least significance difference (LSD). In guiding the calculation, the data were analyzed by using the computer program of SPSS for Window 16.0 version. Findings showed that the learning strategy affected toward cognitive learning achievement of the students. Jigsaw, Reciprocal Teaching (RT), and the combination of Jigsaw-RT strategies could increase the cognitive learning achievement of the students. The combination of Jigsaw-RT strategies was significantly approved in increasing the cognitive learning achievement of the students that were similar to Jigsaw and RT strategies.Â Kata kunci: Jigsaw IV, Reciprocal Teaching, hasil belajar kognitif biologi.Â